Pengaruh Orientasi Belanja dan Kualitas Produk terhadap Minat Beli Belanja Online JD.ID Jakarta - Jonatan, Jonatan; Novitasari, Tantri (Cv. Syntax Corporation Indonesia, 2019)
Begin from early survey that shows how online business is growing rapidly at this time, such thing has stimulates me to do research about factors that affecting online business, particularly for online shopping consumer. I has limited time, then this research only focus on two factors that considered affecting the interest of online shopping, those two factors are the affect of shopping orientation and product quality toward buying interest of online shopping. The source of this research is from pleaded questionnaire to 50 respondents. The research is using descriptive quantitative method. Through data analysis by using SPSS instrument. The result shows the truth of hypothesis that each of shopping orientation and product quality affect partially toward buying interest of online shopping and affect simultaneously as well.